Deep Infiltrating Endometriosis Malignant Invasion of Cervical Wall and Rectal Wall With Lynch Syndrome： A Rare Case Report and Review of Literature - Li, Baoxuan; Wang, Yang; Wang, Yue; Li, Siman; Liu, Kuiran (Frontiers in Oncology, 2022)
Background: Malignant transformation of deep infiltrating endometriosis (DIE) into invasion of the cervix and rectum is quite rare, especially in patients with Lynch syndrome. We report a rare case of a 49-year-old perimenopausal woman with endometrioid carcinoma arising from douglas cul-de-sac invading the cervix and rectum 1 years after Unilateral salpingo-oophorectomy treatment for ovarian endometriosis. The patient's genetic testing showed germline mutations in MSH2, which, combined with the patient's special family history of colorectal cancer of patient, was also thought to be associated with Lynch syndrome(LS). We have analyzed the reported cases of DIE malignant transformation over the last 10 years, and reviewed the relevant literature, in order to strengthen the clinical management of patients with endometriosis, particularly DIE patients, and to reveal a possible correlation between malignant transformation of endometriosis and LS.